Reconstructing Signals of Scintillation Detectors; Russian Journal of Nondestructive Testing; Vol. 58, iss. 1 - Osipov S. P. Sergey Pavlovich; Shchetinkin S. A. Sergey Aleksandrovich; Usachev E. Yu. Evgeny Yurjevich; Chakhlov S. V. Sergey Vladimirovich; Osipov O. S. Oleg Sergeevich (2022, 2022)
Title screen